Effects of beef cattle temperament on feed and water intake - Klahr, Dean E.; Alhberg, C.M; Allwardt, K.; Broocks, A.; Bruno, K.; Taylor, A.; Krehbiel, C.R.; Richards, C.J.; Place, S.E.; DeSilva, U.; VanOverbeke, D.L.; Mateescu, R.G.; et al. (My University, 2017)
Temperament scoring systems encompass a variety of subjective and objective methods. Chute scoring may be the most common subjective method, and is often used by breed associations in their docility genetic evaluations. The most commonly used objective method is exit velocity, which is calculated from the amount of time it takes for an animal to cross 1.83 meters when exiting the working chute. Measurements of temperament collected using both objective and subjective methodologies have been shown to be heritable, and are associated with differences in cortisol levels and average daily gain in the scientific literature. Thus, the objective of this study was to characterize individual animal variation in feed and water intake and evaluate the relationship between beef cattle temperament and feed and water intake. Five objective (exit velocity; EV) and subjective (chute scores; CS) temperament measures were collected on 106 beef steers every 2 weeks over a 70 d feed and water intake test, CS were ordinal, and reflected the temperament of the animal in the chute (1=calm, 4= continuous resistance). EV was calculated using times recorded by electronic eyes (FarmTek). Entry scores were also collected as a control variable and reflected the mechanisms used to encourage the steers to enter the chute. Daily feed and water intakes on each individual animal were recorded using an Insentec system. All data were averaged over the 70 d test period and included length of each feeding/watering event, number of daily intake events, and mean intake. A general linear model was utilized to evaluate the relationships between temperament measures and intake. CS (averaged over the 5 timepoints) and EV (averaged over the 5 timepoints) did not have a significant impact on feed or water intake (P > 0.05). It is possible that this result is due to the fact that most animals in the study were calm, and thus did not include a lot of variation in these traits. Variation in feed and water intake as described by the standard deviation of all daily intake measures was related to overall feed and water intake, and animals that tend to have higher intakes also have higher variability in their daily feed and water intakes (P, 0.05). In addition, the number of daily feed events and the length spent at the bunk are both significant predictors of feed and water intake (P < 0.05).
Keywords: Fall 2017